HOW COMPARISON INFLUENCES THE SUBCONSCIOUS: THE ROLE OF SIMILE IN HYPNOTIC DISCOURSE (Eureka Journal of Language, Culture & Social Change, 2026)
This article explores the role of simile as a central mechanism of hypnotic discourse from a cognitive and psycholinguistic perspective. Building on insights from cognitive linguistics, neurolinguistics, and suggestive linguistics, the study argues that figurative language in hypnotic communication does not merely decorate speech but structures how experience is construed and transformed. Through qualitative analysis of hypnotic and psychotherapeutic texts in Uzbek and Russian, the paper demonstrates how similes grounded in sensory experience and body-based imagery facilitate the re-interpretation of emotions and internal states. The findings suggest that simile operates as implicit suggestive strategy which guides attention, reduce resistance, and influence decision-making at a subconscious level.
Keywords: Hypnotic discourse, simile, influence on subconscious, suggestion